2017
DOI: 10.1002/mnfr.201600686
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of trans‐resveratrol and its metabolites after acute or sustained administration in mouse heart, brain, and liver

Abstract: Scope Trans‐resveratrol is widely studied for its potentially beneficial effects on numerous disorders. It is rapidly metabolized and its metabolites can exhibit biological activity. The present study aimed to investigate whether acute or sustained trans‐resveratrol administration impacted on the distribution of trans‐resveratrol and its metabolites in brain, heart, and liver. Methods and results We used ultra‐HPLC quadrupole‐TOF (UHPLC‐Q‐TOF) in a full‐scan mode to identify and assess large numbers of resvera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
6
25
0
Order By: Relevance
“…An additional novel finding of the present study is that RV conjugation to RVmet was also observed in endothelial cells, mainly to the sulfated metabolite RV3S. Consistent with these findings, the sulfated forms of RV predominate over the glucuronidated conjugates in human plasma and urine, specifically RV3S, while mouse metabolism favors the glucuronidated forms . However, little is known about the predominant metabolites that accumulate in target human tissues, particularly in endothelial cells.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…An additional novel finding of the present study is that RV conjugation to RVmet was also observed in endothelial cells, mainly to the sulfated metabolite RV3S. Consistent with these findings, the sulfated forms of RV predominate over the glucuronidated conjugates in human plasma and urine, specifically RV3S, while mouse metabolism favors the glucuronidated forms . However, little is known about the predominant metabolites that accumulate in target human tissues, particularly in endothelial cells.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Menet et al reported differences in RV and RVmet tissue accumulation in mice after an acute and sustained intake of RV . A single dose of RV resulted in RVmet accumulation in the mouse heart and brain, whereas the sustained intake of RV favored the accumulation of free RV in these tissues, supporting the saturation of the RV metabolic enzymes in tissues.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, trans-resveratrol and relative conjugates were found to be distributed mainly in the liver and kidneys, the primary sites of metabolism and excretion, but radioactivity of 14 C-labeled resveratrol was observed also in the oral cavity, stomach and intestines suggesting a "resveratrol reservoir" of these tissues [14,20]. In accordance with previous investigations, Menet et al confirmed, in an animal model, that after both single dose and sustained resveratrol intake, the distribution was higher in kidneys and the liver, whereas recently the pharmacokinetic analysis by Su and colleagues demonstrated that the major distribution of resveratrol, derivatives and metabolites occurred in the gastrointestinal tract after oral intake [21,22]. As mentioned above, resveratrol undergoes rapid and extensive metabolism, and several studies were conducted in order to identify resveratrol metabolites.…”
Section: Physico-chemical and Pharmacokinetic Properties Of Resveratrolsupporting
confidence: 70%